Legal responsibility towards personal data controller due to dissemination of personal data - Paulus J Karu; Febriansyah Febriansyah (Journal of Law Science, 2024)
Rapid technological developments have negative impacts. One of them is a new crime, namely Cybercrime. One of the objects targeted by cybercrime perpetrators is Personal Data. The PDP Law is a legal regulation that aims to protect the privacy and confidentiality of individuals' personal information. This law is important in regulating the use, collection, processing and dissemination of personal data by entities or organizations. One of them is by applicators who provide e-commerce services who in the PDP Law are referred to as Personal Data Controllers. This research will examine further the responsibilities of personal data controllers in the event of dissemination of personal data belonging to the public. This research method is normative juridical with a statutory approach. The research results show that there are deficiencies in legal regulations regarding personal data controllers located abroad. Thus, the participation of the government and citizens is needed in preventing the spread of personal data.